A high gain and compact transmitarray antenna for Ku-band satellite communications. Issue 5 (4th July 2021) - Iqbal, Muhammad Naeem; Yusoff, Mohd Fairus Mohd; Rahim, Mohammad Kamal A.; Hamid, Mohamad Rijal; Johari, Zaharah; Rahman, Hamood Ur
ABSTRACT: This work focuses on designing a low-profile frequency selective surface transmitarray antenna at 12 GHz using a four-layer Split Ring Resonator structure. The parametric analysis shows a high transmission coefficient magnitude of −2.38 dB and 349-degrees phase range. X-band horn antenna is used as a feed source to illuminate the Frequency Selective Surface (FSS) transmitarray layers. Each FSS layer is comprised of 121 elements. The measured results show a wide impedance bandwidth of 35%, a high gain value of 21.9 dBi and 11.6% 1-dB bandwidth. The proposed design can be used in high gain array antenna applications, particularly Ku band Satellite communication systems.